Backward Chaining Model for Identifying Learning Difficulties Experienced by Special Needs Children - Fiati, Rina; Kurniati, Diah (Universitas Negeri Semarang, 2022)
Identification of learning difficulties is the most important process because it determines the next step in conducting an assessment especially for students with special needs. The first step that needs to be taken in determining the learning difficulties of children with special needs is through identification, where each student has a different character. The purpose of the research is to identfy learning difficulties faced by children with special needs by using backward chaining model and give solutions to learning difficulties. The study's findings indicate that the main factor causing learning challenges for children with special needs is an internal component coming from the students themselves, namely their motivation (75%). The second component is an external factor that has to do with how parents educate their special needs children (25%). To solve the problems, students should have a high motivation in studying and parents should change the way they educate their children. It is suggested that parents should give more attention on students’ academic progress